Effect of transition metal cations on commensurate freezing of n-hexane confined in micropores of ZSM-5 - Hercigonja Radmila (Journal of the Serbian Chemical Society, 2015)
Besides its importance concerning fundamental studies on gas adsorption in narrow pores, investigation of commensurate freezing of fluid within the zeolite is of practical importance in application of zeolite in the process of adsorption, separation and catalysis. In this work the adsorption of n-hexane on HZSM-5 and its transition metal ion-exchanged modified forms was studied at 303 K by means of microcalorimetry. The thermal molar entropies of adsorption were calculated and thus, the freezing like behaviour of n-hexane inside the structure of zeolite as a confinement media was noticed. This effect is governed by the attractive interactions between n-hexane molecules and the pore walls, and is also influenced by the length of the pores and the nature of charge-balancing cations. Among the investigated zeolites, solid like phase of n-hexane in the pores of zeolites with Fe2+ ions is the most like a solid n-hexane bulk, while the presence of Cu2+ ions contribute to the lowest ordering obtained solid like phase of n-hexane. [Projekat Ministarstva nauke Republike Srbije, br. 172018]